SENI BACA AL-QURAN: METODE EFEKTIF DALAM PEMBELAJARAN AL-QURAN HADITS - Maskur, Maskur (Pascasarjana IAIN Kudus, 2019)
Reading is part of the learning process. Reading will support learning activities carried out both in the classroom and in the Islamic boarding school. Learning in reading the Koran basically must pay attention to the main principles that need to be understood by every teacher. This is because learning to read the Qur'an is certainly different from learning to read books, novels and other reading. The purpose of this study is to look at the implementation of the learning of the art of reading the Qur'an in the learning of AlQur'an Hadith. Thus it will be seen clearly how the application of the art of reading the Koran is seen from its effectiveness in learning Al-Quran Hadith.